The Influence Of Media And Group Influence On Generation Y Attitudes In The Use Of Beauty Products Mediated By Subjective Norms - Purnama, Jesicha Aulya; Arief, Muhammad; Diatmika, Anak Agung Ketut; Edastama, Primasatria (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Media influence important For spread information about product beauty , while group influence influence consumer in follow standard group before buying . Subjective norms mediate influence second variable the to behavior consumers , depending on the reaction friends , family and loved ones to trends from media and group influence . The goal from study This is For analyze connection media influence , group influence , and subjective norms to attitudes Generation Y female consumers in use skincare product , in Bekasi City area. Research This done with descriptive quality with method quantitative . Data in study This done from 168 respondents user Scintifi . Conceptual model study analyzed use Structural Equation Model Partial Least Square (SEM-PLS). Research result show that media influence and group influence influential positive to subjective norms consumer woman generation Y on beauty products . Suggestions for study next in the future come can covers consideration various product skin care others . Besides that , researchers can also use or add other relevant variables . Then , future research​ should do research on different regional scopes . Keywords :​ Media Influence, Group Influence, Subjective Norms, Attitudes